SHP2 inhibitor specifically suppresses the stemness of KRAS-mutant non-small cell lung cancer cells - Lei Jiang; Weiping Xu; Yi Chen; Yue Zhang (Artificial Cells, Nanomedicine, and Biotechnology)
RAS mutations are frequent in non-small cell lung cancer (NSCLC). However, targeting RAS or the downstream/upstream effectors, such as tyrosine kinase inhibitors (TKIs), has been proved to be difficult. Here, we found that the stemness of KRAS-mutant NSCLC cells but not the KRAS-wild type NSCLC cells was promoted by TKIs treatment, as evident by the increase of ALDH1 activity, stemness marker expression and spheroid formation ability. Notably, SHP2 activation was found in KRAS-mutant NSCLC cells with TKIs treatment, as judged by the increase of tyrosine 542 phosphorylation (pSHP2 Y542), which activates the RAS/MEK/ERK pathway. On the contrary, inhibition of MEK was followed by a SHP2 activation in KRAS-mutant NSCLC cells. Additionally, inhibition of SHP2 attenuates the enhanced stemness of KRAS-mutant NSCLC cells induced by TKIs, characterized by decreasing ALDH1 activity, stemness marker expression and spheroid formation capacity, while had little effects on cell viability. Finally, we revealed that SHP2 inhibitor increased the sensitivity of TKIs and chemotherapy, which was potentiated by MEK inhibition. Our results suggest a possibility of using a combination of SHP2 inhibitor and TKIs for KRAS-mutant NSCLC treatment.